(untitled) (Revista de Medicina Clinica, 2025)
Lynch syndrome (LS), also known as hereditary nonpolyposis colorectal cancer (HNPCC), is considered the most common type of hereditary colon cancer with autosomal dominant inheritance. It has been reported to have an 80% risk of developing colorectal cancer, 60% risk of endometrial cancer, and, depending on the variant, increased risk of other primary cancers such as gastric, ovarian, urothelial, biliary tract, cerebral, small intestine, cutaneous, pancreatic. The identification of carriers of pathogenic mutations in MMR genes (MLH1, MSH2, MSH6, PMS2) is important for the timely detection of SL-associated cancers. The Amsterdam II criteria should be implemented, which identifies patients with a high suspicion of LS, to complement it with genetic studies, including microsatellite instability, to perform timely detection, and to be able to reduce complications and mortality. We present the case of a male patient with a family history of colon, endometrial and ovarian cancer in his first- and second-degree family, respectively, with three months of evolution of iron deficiency anemia and exacerbated rectorrhagia, where, after endoscopic studies, histopathological study reports moderately differentiated adenocarcinoma of the colon with high detection of microsatellite instability, genetic studies are extended with diagnosis of Lynch Syndrome., and it is decided to start FOLFOX chemotherapy for neoadjuvant treatment. Lynch syndrome is an atypical pathology with a low presentation rate, which contributes to the medical literature to reinforce the importance of family history and genetics in order to expand knowledge about the heterogeneity of LS, helping to optimize screening, diagnostic and treatment strategies.